Optical and structural properties of ZnO nanorods grown by pulsed laser deposition without a catalyst - Kaydashev, V.E.
Pulsed laser deposition without a catalyst is used to grow ZnO nanorods less than 10 nm in diameter. The structure of the rods is studied by Raman scattering during excitation in the visible and UV regions. The temperature dependences of exciton spectra and the behavior of green luminescence are investigated in the temperature range 10–280 K. At room temperature, the luminescence intensity of the ZnO nanorods in the exciton region is higher than the green luminescence intensity by a factor of 7.8.